The Role of Intellectual Capital and Core Competencies in Building Competitive Advantage in Higher Education - Ike Yuni Hartanti; Dwi Irawan; Ahmad Juanda (Universitas Pendidikan Ganesha, 2024)
This study examines the relationship between intellectual capital, core competencies, and competitive advantage within higher education institutions in Indonesia. These institutions are pivotal in adapting to globalization and enhancing educational competitiveness. Despite existing research, there remains a gap in understanding how these elements interact dynamically within the Indonesian context, particularly how intellectual capital directly and indirectly influences competitive advantage through core competencies. Our population includes all universities listed in the 2023 Webometrics world university rankings, focusing on lecturers involved in planning and administrative tasks. A simple random sampling method was employed to select the sample. Data were collected using self-administered questionnaires and analyzed through Structural Equation Modeling (SEM) via Partial Least Square (PLS) 3.0 software. The findings reveal that intellectual capital significantly influences competitive advantage, mediated by core competencies unique to Indonesian higher education. This research offers insights for stakeholders, including education managers, policymakers, and academics, to develop strategies that enhance competitive positioning by optimizing intellectual capital and evolving core competencies aligned with industry needs and societal demands in the digital era. This study fills the identified research gap by providing empirical evidence and strategic insights into the interplay of these critical factors.